Wire-guided biliary cannulation: a comprehensive approach to a set of techniques. Issue 11 (November 2019) - Cennamo, Vincenzo; Bassi, Marco; Landi, Stefano; Binda, Cecilia; Fabbri, Carlo; Ghersi, Stefania; Gasbarrini, Antonio
Abstract : Biliary cannulation represent a challenge for the endoscopists that approach to endoscopic retrograde cholangiopancreatography, with non-negligible rate of failure even in expert hands. In order to achieve the biliary tree, two main technique are nowadays mainly used, namely the contrast-assisted cannulation and the wire-guided cannulation (WGC) techniques. The WGC technique is widely used because it seems to be related to higher success rate of cannulation of the common bile duct and, at the same time, to lower rates of complications. Particularly, this approach is associated with lower risk of post endoscopic retrograde cholangiopancreatography pancreatitis, although the pathogenesis of this adverse event is still not completely understood. The outspread of this technique among endoscopists promoted the development of different methods of performing WGC-assisted endoscopic retrograde cholangiopancreatography, such as the touch technique, the no-touch technique and the double guide-wire cannulation. Furthermore, the variety of guide wires and accessories, with their different characteristics, contribute to make the scenario extremely heterogeneous. To date, the published studies did not highlight which is the best strategy that maximizes the rate of success and minimizes the percentage of complications, even because the experience of the operator represents an important variable that conditions the outcomes. The aim of this review is to define state of the art in WGC technique, in order to better understand the possible advantages in using this approach and to bring to light the possible area that may be object of further studies.